Ten-year trends in adverse drug reaction–related hospitalizations among people with dementia. (March 2022) - Zaidi, Anum Saqib; Peterson, Gregory M.; Bereznicki, Luke R.E.; Curtain, Colin M.; Salahudeen, Mohammed S.
Aim: Trends in the incidence of adverse drug reaction (ADR)–related hospitalizations have been studied in the general population, but not specifically in people with dementia. This study aimed to investigate trends in the incidence of ADR-related hospitalizations among people with dementia, and identify the most commonly implicated drugs and diagnoses in these admissions. Methods: This study utilized the administrative data of all adults admitted to the four major public hospitals of Tasmania, Australia, with a primary or secondary diagnosis of dementia from July 2010 to December 2019. ADR-related hospitalizations were identified by using diagnosis-based and external cause codes. The Cochran–Armitage test was used to examine trends in the incidence of ADR-related hospitalizations. Results: Of the 7552 people with dementia admitted to the hospital at least once within the study period, 1775 (23.5%) experienced at least one ADR-related hospitalization. The estimated annual incidence of ADR-related hospitalizations increased 18% (1484–1760 per 100, 000 population with dementia, p for trend <0.05) from 2010 to 2019. For those ADR-related admissions with a drug code recorded, 19.3% were due to antithrombotics and 11.5% to antihypertensives. The most frequent ADR-related admission diagnoses were renal diseases (72.9%). Length of hospital stay and in-hospital mortality were both significantly greater for ADR-related, relative to non-ADR-related, admissions (median 7 versus 5 days and 11% versus 6.7%, respectively; p < 0.001). Conclusion: The annual incidence of ADR-related hospitalizations in people with dementia increased between 2010 and 2019. Antithrombotics were the most commonly implicated drug class. The ADR-related hospitalizations were associated with increased length of stay and greater mortality. Plain Language Summary: Adverse drug reaction–related hospitalizations among people with dementia Introduction: This study aimed to investigate trends in hospitalizations associated with medication problems among people with dementia, and identify the most commonly implicated drugs and diagnoses in these admissions. Methods: This study utilized the administrative data of all adults admitted to the four major public hospitals of Tasmania, Australia, with dementia from July 2010 to December 2019. Results: The annual incidence of hospitalizations associated with medication problems among people with dementia increased nearly 20% over 10 years. The length of hospital stay and in-hospital mortality were significantly greater for hospitalizations related to medication problems. Conclusion: The incidence of hospitalizations associated with medication problems in people with dementia increased between 2010 and 2019.